Homochiral lithium amides for the asymmetric synthesis of beta-amino acids - Davies, S; Garrido, N; Kruchinin, D; Ichihara, O; Kotchie, L; Price, P; Mortimer, A; Russell, A; Smith, A (2006)
Secondary homochiral lithium amides derived from α-methylbenzylamine undergo highly diastereoselective conjugate additions to a range of α,β-unsaturated esters. The corresponding β-amino acids are readily liberated by successive N-debenzylation and ester hydrolysis, furnishing (R)-β-amino butyric acid, (R)-β-amino pentanoic acid, (S)-β-leucine, (R)-β-amino octanoic acid, (S)-β-phenylalanine, (S)-β-tyrosine methyl ether, (S)-β-tyrosine hydrochloride and (S)-β-(2-methoxyphenyl)-β-amino propanoic acid in high yields and high ee. The application of this procedure to the synthesis of the natural products (R)-β-DOPA and (R)-β-lysine is demonstrated. The development of a simplified one-pot reaction protocol applicable to the multi-gram scale synthesis of homochiral β-amino esters is also delineated. © 2006 Elsevier Ltd. All rights reserved.